Acupuncture Attenuated Vascular Dementia–Induced Hippocampal Long-Term Potentiation Impairments via Activation of D1/D5 Receptors. Issue 4 (April 2017) - Ye, Yang; Li, Hui; Yang, Jing-Wen; Wang, Xue-Rui; Shi, Guang-Xia; Yan, Chao-Qun; Ma, Si-Ming; Zhu, Wen; Li, Qian-Qian; Li, Tian-Ran; Xiao, Ling-Yong; Liu, Cun-Zhi
Abstract : Background and Purpose—: Emerging evidence suggests that acupuncture could improve cognitive impairment in vascular dementia by enhancing synaptic plasticity in the hippocampus. The purpose of this study is to investigate whether dopamine, a key mediator of synaptic plasticity, is involved in this cognitive improvement. Methods—: Vascular dementia model was established by bilateral common carotid arteries occlusion in male Wistar rats. Three days after the operation, animals received acupuncture treatment for 2 weeks, once daily. The D1/D5 receptors antagonist SCH23390 was administered intraperitoneally 15 minutes before each acupuncture treatment. Morris water maze was examined after acupuncture. Long-term potentiation was studied by an electrophysiological technique. Dopamine and metabolites levels were detected by microdialysis and high-performance liquid chromatography from brain tissue. The expression of D1R and D5R was analyzed by immunofluorescence. Results—: Acupuncture remarkably reversed cognitive deficits in 2-vessel occlusion model (2VO) rats, and the acupuncture points Zusanli (ST36) and Baihui (GV20) were confirmed to be the most effective combination. Electrophysiological recording data showed that 2VO-induced impairments of long-term potentiation were prevented by acupuncture. In addition, acupuncture promoted the release of dopamine and its major metabolites in the hippocampus of 2VO rats. The immunofluorescence experiment showed that the decrease of D1R and D5R in hippocampal dentate gyrus region of 2VO rats was reversed by acupuncture. Furthermore, we found that the effects of acupuncture against 2VO-induced impairments in cognition and synaptic plasticity were abolished by SCH23390. Conclusions—: Improvement in cognition and hippocampal synaptic plasticity induced by acupuncture was achieved via activation of D1/D5 receptors in 2VO rats. Abstract : Supplemental Digital Content is available in the text.